Perancangan Brosur Sebagai Media Promosi Ekowisata Mangrove Medokan Ayu Surabaya - Nanang Setiyoko Nanang; Miftahul Adi Suminto (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2024)
The current problem is that  Medokan Ayu Surabaya Mangrove Ecotourism is not widely known to the public inside and outside Surabaya city. Promotion is only  by word of mouth so the scope of  promotion is not wide. Medokan Ayu Surabaya Mangrove Ecotourism needed a safe way to introduce itself to the public. We wanted to use community-oriented promotional materials to promote this type of ecotourism while respecting government health regulations. This design uses SWOT analysis to explore and solve the problems faced by Medokan Ayu Surabaya Mangrove Ecotourism. The researchers also reinforced the SWOT analysis method used by using  qualitative methods, such as observations and in-depth interviews. Furthermore, the researchers used theory in the fields of social media, marketing communications, and marketing strategy to design promotions for  Medokan Ayu Surabaya Mangrove Ecotourism. The researchers also developed the visual identity as part of the  design to promote Medokan Ayu Surabaya Mangrove Ecotourism. The results of this design include promotional materials and logos specifically designed to support the promotion of Medokan Ayu Surabaya Mangrove Ecotourism.